Simple cake : all you need to keep your friends and family in cake : 10 cakes, 15 toppings, 30 cake-worthy moments - Williams, Odette (Ten Speed Press, 2019)
A nostalgic ode to the joy of homemade cake, beautifully photographed and with easy mix-and-match recipes for a sweet lift any day of the week--